1996
DOI: 10.1111/j.1439-0523.1996.tb00908.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of low linolenic acid content on seed yield of winter oilseed rape (Brassica napus L.)

Abstract: An essential quaUty improvement of rapeseed oil can be obtained by reduction of its linolenic acid (C18:3) content from about 10% to less than 3% of the total fatty acids. Genotypes low in C18:3 have been developed by mutagenesis. The initial summer rapeseed mutant had been low yielding and highly susceptible to various diseases. It has been debated whether the low C18:3 character can be successfully combined with high seed yield for physiological reasons. Therefore, the low linolenic character of mutant M48 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 18 publications
1
33
0
1
Order By: Relevance
“…Improvement of both oil and meal in oilseed rape by reducing erucic acid content of oil (canola quality) and glucosinolate content of meal are two most prominent milestones contributing to the expansion of world oilseed rape acreage from less than 10 million hectares in the early 1970s to more than 27 million hectares in 2005 (FAO-STAT 2007). Moreover, high oleic (Schierholt et al 2001) and low linolenic (Ru¨cker and R¨obbelen 1996) oilseed rape represent further improvements of nutritional value and oxidative stability. Relevant changes in fatty acid composition have also been achieved in sunflower, soybean and linseed (Table 1.3).…”
Section: Recent Milestones In Oil Crop Breedingmentioning
confidence: 99%
“…Improvement of both oil and meal in oilseed rape by reducing erucic acid content of oil (canola quality) and glucosinolate content of meal are two most prominent milestones contributing to the expansion of world oilseed rape acreage from less than 10 million hectares in the early 1970s to more than 27 million hectares in 2005 (FAO-STAT 2007). Moreover, high oleic (Schierholt et al 2001) and low linolenic (Ru¨cker and R¨obbelen 1996) oilseed rape represent further improvements of nutritional value and oxidative stability. Relevant changes in fatty acid composition have also been achieved in sunflower, soybean and linseed (Table 1.3).…”
Section: Recent Milestones In Oil Crop Breedingmentioning
confidence: 99%
“…Following trierucin analysis remaining parts of the oil samples were transferred to a new tube and left over night on a hot plate at 37.5°C to evaporate the solvent. Fatty acids composition were analyzed by GLC according to Rücker and Röbbelen (1996). Trierucin and fatty acids are expressed as % of the sum of all triglycerides and fatty acids, respectively.…”
Section: Seed Quality Analysismentioning
confidence: 99%
“…In rapeseed breeding, efforts have made for many years focusing on increasing the oleic acid content. In Germany, mutation experiments were started about 20 years ago and first mutant with HO acid content was selected by Rücker and Röbbelen (1996). Genetic studies confirmed that the selected mutant line was inherited by single gene in an additive manner (Schierholt et al 2001).…”
Section: Development Of High Oleic Acid Oilseed Rape (Hoar)mentioning
confidence: 99%